Contribution of Incentives and School Climate to Teacher's Job Satisfaction Senior High School - Hasni Julidawati; Nurhizrah Gustituati; Yahya Yahya; Irsyad Irsyad (CV. AFDIFAL MAJU BERKAH, 2023)
Based on the pre-survey results, it is illustrated that the job satisfaction of Kampar Regency Senior High School teachers is still low. It was assumed that it dealt with two issues including unfulfilled incentives and unconducive school climate. Thus, it is required to conduct research to test the truth. This study aims to reveal the contribution of incentives and school climate to the job satisfaction of teachers at Kampar Regency High School. The hypotheses put forward in this study are: (1) incentives contribute to teachers' job satisfaction, (2) school climate contributes to teacher' job satisfaction, (3) incentives and school climate contribute to teachers' job satisfaction. The population in this study were 687 teachers with PNS status at Kampar Regency State High School. The samples were chosen through two different techniques, the first technique was cluster random sampling based on the distance from the school to the city center, and it was obtained 6 schools with 205 teachers. The second was stratified proportional random sampling based on strata, and it was obtained 27 teachers as the sample. The research instrument used is the assessment scale and the Likert Scale Questionnaire model which has been tested for its validity and reliability. The research data were analyzed using correlation and regression techniques. The research finding show 3 main points: (1) incentives contribute to teachers' job satisfaction by 51.6%, (2) school climate contributes to teachers' job satisfaction by 22.4%, (3) incentives and school climate jointly contribute to teachers' job satisfaction of 70.9%. The achievement level of the teachers' job satisfaction score is 83.95% which is considered as satisfied category, and for incentives 83.44% is in the good category while for the school climate 84.10 from the ideal score is in the conducive category. To conclude, the findings imply that incentives and school climate are two factors that can increase teachers' job satisfaction, apart from other factors.